Espanhóis no interior de São Paulo: múltiplas possibilidades de incorporação - Silva, João Paulo da (Universidade Federal de São Carlos, 2020)
This thesis aims to understand the multiple modes of incorporation of Spanish immigrants in São Paulo between 1890 and 1940, by analysing six different contexts (cities) in the provinces of this state: Sorocaba, Franca, Catanduva, Cafelândia, Bauru and Olímpia. To outline the multiple possibilities of incorporation of the group, the main issues we analyse are: its numerical size, the resources that were mobilized, the facilities and difficulties imposed by each locality, the possibilities of upward mobility, the arrangements with the local elites, and the investments in the ethnic identity, among others. Based on diversified theoretical contributions from migratory studies, we seek to make an analysis of different trajectories of Spaniards, demonstrating from a set of heterogeneous cases the multiple forms of incorporation carried out by the group.
Spaniards in the provinces of São Paulo: the multiple modes of incorporation
Keywords: Imigração espanhola; Espanhóis no interior paulista; Modos de incorporação de imigrantes; Estudos migratórios; Identidade étnica espanhola; Percursos migratórios; Spanish immigration; Spaniards in the provinces of São Paulo; Immigrant modes of incorporation; Spanish ethnic identity; Migratory paths; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS